Macroeconomic Facts. Georgia - Demur Giorkhelidze (European Scientific Journal, ESJ, 2023)
The article discusses and systematizes the macroeconomic facts that have been formed in Georgia over the past few decades and creates a common basis for understanding and comprehending the processes of economic growth and development. These facts give us the opportunity to understand what the possibilities for economic growth might be in the medium and long term perspective (20-30 years), on what basis macroeconomic policy should be built and growth forecasts should be made, at least, assessment on an acceptable level. Due to the peculiarities of the modern economy, this is a very complex, but possible issue with the use of modern means (methods) of assessment.